Antioxidant and Antitumor Potential of Micropropagated Balkan Endemic Sideritis scardica Griseb - Krasimira Tasheva; Ani Georgieva; Petko Denev; Lyudmila Dimitrova; Margarita Dimitrova; Svetlana Misheva; Polina Petkova-Kirova; Maria Lazarova; Maria Petrova (Plants, 2023)
Sideritis scardica Griseb. is a critically endangered Balkan endemic species, known for its antioxidant, neuroprotective and anti-inflammatory properties. The aim of the present study was to detail an efficient protocol for the micropropagation of S. scardica. In vitro cultures were initiated from the shoot tips of 40 days-old in vivo seedlings and the effects of different plant growth regulator treatments were examined. A Murashige and Skoog nutrient medium (MS) containing 1 mg/L zeatin and 0.1 mg/L indole-3-acetic acid (IAA) proved to be the most efficient for shoot multiplication as it produced quality, vigorous shoots with a mean number of six shoots per explant. For the first time, the antioxidant and antitumor activities of extracts from in vitro-obtained plants were evaluated. In vitro cultivated plants grown in the field revealed a higher total polyphenol content (3929.1 ± 112.2 mg GAE/100 g vs. 3563.5 ± 52.8 mg GAE/100 g) and higher ORAC antioxidant activity (1211.6 ± 27.3 µmol TE/g vs. 939.9 ± 52.4 µmol TE/g) than in situ cultivated plants. A comparison of the antitumor activities of extracts from in vitro propagated shoots, field-grown in vitro-obtained plants and in situ plants on HeLa (cervical adenocarcinoma), HT-29 (colorectal adenocarcinoma) and MCF-7 (breast cancer) human cancer cell lines showed that in vitro propagated shoots had a significant concentration-dependent cytotoxic effect on the cervical adenocarcinoma cell line HeLa, while the field-grown in vitro-obtained and in situ-collected samples induced the highest reduction in the viability of the mammary carcinoma cell line MCF-7. In both cases, the cells of the control non-tumor cell line, BALB/3T3, were significantly less affected. The results showed that the in vitro multiplication protocol ensured the obtainment of numerous plants with antioxidant and antitumor potential.